Improvisation: Its Nature and Practice in Music - Bailey, Derek (Boston, MA Da Capo, 1992)
Derek Bailey's Improvisation, originally published in 1980, and here updated and extended with new interviews and photographs, is the first book to deal with the nature of improvisation in all its formsIndian music, flamenco, baroque, organ music, rock, jazz, contemporary, and free music. By drawing on conversations with some of todays seminal improvisersincluding John Zorn, Jerry Garcia, Steve Howe, Steve Lacy, Lionel Salter, Earle Brown, Paco Peña, Max Roach, Evan Parker, and Ronnie ScottBailey offers a clear-eyed view of the breathtaking spectrum of possibilities inherent in improvisational practice, while underpinning its importance as the basis for all music-making.
Originally published in 1980
Keywords: Improvisation